2000
DOI: 10.1021/bi000786d
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Catalytic Triad of Escherichia coli Outer Membrane Phospholipase A

Abstract: Escherichia coli outer membrane phospholipase A (OMPLA) is an integral membrane enzyme. OMPLA is active as a homodimer and requires calcium as a cofactor. The crystal structures of the monomeric and the inhibited dimeric enzymes were recently determined [Snijder, H. J., et al. (1999) Nature 401, 717-721] and revealed that OMPLA monomers are folded into a 12-stranded antiparallel beta-barrel. The active site consists of previously identified essential residues Ser144 and His142 in an arrangement resembling the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Third, mutagenesis showed that Glu-140 is important for PagL activity, although not essential, because residual activity was detected after its substitution by Ala. In OMPLA, Asn-156 is not essential either, because Asn156Ala substitution reduced OMPLA activity Ϸ20-fold (18). A possible explanation is that OMPLA, and probably also PagL, has a highly functional oxyanion hole that can partly compensate for the loss of the acidic residue.…”
Section: Discussionmentioning
confidence: 99%
“…Third, mutagenesis showed that Glu-140 is important for PagL activity, although not essential, because residual activity was detected after its substitution by Ala. In OMPLA, Asn-156 is not essential either, because Asn156Ala substitution reduced OMPLA activity Ϸ20-fold (18). A possible explanation is that OMPLA, and probably also PagL, has a highly functional oxyanion hole that can partly compensate for the loss of the acidic residue.…”
Section: Discussionmentioning
confidence: 99%
“…In some systems, however, the Asp simply serves to maintain the correct position of the active site histidine. Indeed, in cysteine proteases, a conserved Asn residue (e.g., Asn175 in papain) serves this very purpose (35) and Asn156 appears in the hydrolase catalytic triad of E. coli outer membrane phospholipase A (15). We assume that the role of Asp363 is to stabilize the appropriate His263 rotamer or tautomer in SpoIVB catalysis, a function that could potentially be performed by Asn.…”
Section: Discussionmentioning
confidence: 99%
“…Initial OMPLA activities at various calcium concentrations could be ¢tted to a hyperbolic saturation curve to yield a calcium a⁄nity of 18 WM [17]. The ¢nal OMPLA activities obtained with Eq.…”
Section: Kinetic Modelmentioning
confidence: 99%